PROFIL NILAI-NILAI KARAKTER DITINJAU DARI PENDIDIKAN DAN PEKERJAAN ORANGTUA SISWA DI SMP NEGERI 8 PEKANBARU T.P. 2016/2017 - Resida Esnawati S; Elni Yakub; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this research is to describe and analyze the character values in terms of education and parents’s work of students of junior high school. This research is based on descriptive analysis and questionnaire is used as tools with respect to data gathering purpose. Total sample is 186 students and collected by using random technique. The collected data are then analyzed according to descriptive analysis scheme in form percentage. Result shows that the education level of Father and Mother graduated / did not graduate. The graduate showed a better proportion of character values compared to the level of education of Father and Mother graduated from college, graduated from high school, graduated / did not finish junior high school, and Graduated / did not finish primary school. Judging from the type of work Dad shows that the type of Dad's job as a civil servant shows a better proportion of character values than the job type of Father as a private employee / employee, educator, retired, TNI / Polri, self-employed, farmer, and trader. While the type of work of Mother as a private employee / employee shows the proportion of character values better than the type of work of the mother as educators, civil servants, IRT, entrepreneurs, and traders.Keywords : character values, level of education, type of work